ISRLIYYT DAN BIAS GENDER DALAM PENAFSIRAN AL-QURAN - Norhidayat Norhidayat (Jurnal Ilmiah Ilmu Ushuluddin, 2012)
This paper tries to explore about the Israilliyyat and gender bias in interpretating theAlquran. This paper emphasizes that the infiltration the Isra liyyt narrations intafseer books were not necessarily lead to the interpretation of al-Qur an in thosebooks were related to the gender bias. This conclusion denied the Muslim feministinterpretation that in the classic books there are some gender-biased interpretation whichare caused by infiltration of Israliyyt narrations. Special studies of Isra liyyt andconcept of women ceation in al-Tabari interpretation strengthens the conclusions of thispaper and also denied the allegations of Muslim feminists popularized.